Decreased SynMuv B gene activity in response to viral infection leads to activation of the antiviral RNAi pathway in C. elegans. - Ashwin Seetharaman; Himani Galagali; Elizabeth Linarte; Mona H X Liu; Jennifer D Cohen; Kashish Chetal; Ruslan Sadreyev; Alex J Tate; Taiowa A Montgomery; Gary Ruvkun (PLoS Biology)
RNA interference (RNAi) mediates antiviral defense in many eukaryotes. Caenorhabditis elegans mutants that disable RNAi are more sensitive to viral infection. Many mutants that enhance RNAi have also been identified; these mutations may reveal genes that are normally down-regulated in antiviral defense. About one-third of the score of mutants that enhance RNAi are in synMuv B genes, identified 30 years ago in unrelated screens for increased growth factor signaling. Many synMuv B genes encode dREAM complex chromatin-regulatory proteins found in nearly all animals and plants. We show that mRNAs which are highly induced in synMuv B mutants are congruent with those induced by Orsay RNA virus infection, suggesting that the enhanced RNAi of synMuv B mutants may also be triggered by down-regulation of synMuvB gene activity in an Orsay virus infection of wild type. The multivulval (Muv) phenotype of synMuv B mutants requires the presence of a second nematode-specific synMuv A gene mutation, but the enhanced RNAi of synMuv B mutants does not require a second synMuv A mutation. To test if Orsay viral infection down-regulates synMuv B gene activity, we infected a single synMuv A mutant with Orsay virus and found that a Muv phenotype could be induced. Thus, decreased synMuv B gene activity is part of the normal C. elegans viral defense response. In support of the model that decreased syn- Muv B gene activity enhances antiviral response, we found that synMuv B mutants have 50 to 100× lower viral RNA levels during an Orsay virus infection than wild type. Thus down-regulation of synMuv B activity to enhance RNAi is a key component in the defense response to viral infection. Small RNA deep sequencing analysis of dREAM complex mutants revealed siRNA profiles indicative of such a response. Thus, the pan-eukaryotic synMuv B genes constitute an element in C. elegans antiviral defense which is conserved across many eukaryotes where it also may act in viral defense. The enhanced RNAi and conservation of the dREAM complex mutants suggests new therapeutic avenues to boost antiviral defenses.